Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Sure, let's solve for [tex]\( x \)[/tex] from the equation
[tex]\[ \log(7x + 3) + 2 \log(5) = 2 + \log(x + 3) \][/tex]
Here's a detailed, step-by-step solution:
1. Simplify the logarithmic terms involving constants:
We know that [tex]\( a \log b = \log(b^a) \)[/tex]. Hence, [tex]\( 2 \log(5) = \log(5^2) = \log(25) \)[/tex].
Therefore, the equation becomes:
[tex]\[ \log(7x + 3) + \log(25) = 2 + \log(x + 3) \][/tex]
2. Combine the logarithmic terms on the left-hand side:
Using the property [tex]\( \log a + \log b = \log(ab) \)[/tex], we can combine [tex]\( \log(7x + 3) \)[/tex] and [tex]\( \log(25) \)[/tex]:
[tex]\[ \log((7x + 3) \cdot 25) = 2 + \log(x + 3) \][/tex]
This simplifies to:
[tex]\[ \log(175x + 75) = 2 + \log(x + 3) \][/tex]
3. Isolate the logarithmic expressions:
Next, we want to isolate the logarithmic terms on each side of the equation. Subtract [tex]\( \log(x + 3) \)[/tex] from both sides:
[tex]\[ \log(175x + 75) - \log(x + 3) = 2 \][/tex]
4. Combine the left-hand side using the properties of logarithms:
Using the property [tex]\( \log \frac{a}{b} = \log(a) - \log(b) \)[/tex]:
[tex]\[ \log \left( \frac{175x + 75}{x + 3} \right) = 2 \][/tex]
5. Exponentiate both sides to eliminate the logarithm:
Recall that if [tex]\( \log(a) = b \)[/tex], then [tex]\( a = 10^b \)[/tex]. Here, we use the natural logarithm base, [tex]\( e \)[/tex], which means [tex]\( e^{\log(a)} = a \)[/tex] and [tex]\( e^2 = e^2 \)[/tex].
[tex]\[ \frac{175x + 75}{x + 3} = e^2 \][/tex]
6. Solve the resulting algebraic equation:
Now we need to solve for [tex]\( x \)[/tex]. Set up the equation:
[tex]\[ 175x + 75 = e^2 (x + 3) \][/tex]
Expand and rearrange to get all terms involving [tex]\( x \)[/tex] on one side:
[tex]\[ 175x + 75 = e^2 x + 3e^2 \][/tex]
[tex]\[ 175x - e^2 x = 3e^2 - 75 \][/tex]
[tex]\[ x (175 - e^2) = 3e^2 - 75 \][/tex]
Finally, solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{3e^2 - 75}{175 - e^2} \][/tex]
Thus, the solution for [tex]\( x \)[/tex] in the given equation is:
[tex]\[ x = \frac{3(e^2 - 25)}{175 - e^2} \][/tex]
This result can also be simplified further but relies on the values calculated within the problem setting.
Therefore,
[tex]\[ x = \frac{3 \left(e^2 - 25 \right)}{175 - e^2} \][/tex]
is the final solution for [tex]\( x \)[/tex].
[tex]\[ \log(7x + 3) + 2 \log(5) = 2 + \log(x + 3) \][/tex]
Here's a detailed, step-by-step solution:
1. Simplify the logarithmic terms involving constants:
We know that [tex]\( a \log b = \log(b^a) \)[/tex]. Hence, [tex]\( 2 \log(5) = \log(5^2) = \log(25) \)[/tex].
Therefore, the equation becomes:
[tex]\[ \log(7x + 3) + \log(25) = 2 + \log(x + 3) \][/tex]
2. Combine the logarithmic terms on the left-hand side:
Using the property [tex]\( \log a + \log b = \log(ab) \)[/tex], we can combine [tex]\( \log(7x + 3) \)[/tex] and [tex]\( \log(25) \)[/tex]:
[tex]\[ \log((7x + 3) \cdot 25) = 2 + \log(x + 3) \][/tex]
This simplifies to:
[tex]\[ \log(175x + 75) = 2 + \log(x + 3) \][/tex]
3. Isolate the logarithmic expressions:
Next, we want to isolate the logarithmic terms on each side of the equation. Subtract [tex]\( \log(x + 3) \)[/tex] from both sides:
[tex]\[ \log(175x + 75) - \log(x + 3) = 2 \][/tex]
4. Combine the left-hand side using the properties of logarithms:
Using the property [tex]\( \log \frac{a}{b} = \log(a) - \log(b) \)[/tex]:
[tex]\[ \log \left( \frac{175x + 75}{x + 3} \right) = 2 \][/tex]
5. Exponentiate both sides to eliminate the logarithm:
Recall that if [tex]\( \log(a) = b \)[/tex], then [tex]\( a = 10^b \)[/tex]. Here, we use the natural logarithm base, [tex]\( e \)[/tex], which means [tex]\( e^{\log(a)} = a \)[/tex] and [tex]\( e^2 = e^2 \)[/tex].
[tex]\[ \frac{175x + 75}{x + 3} = e^2 \][/tex]
6. Solve the resulting algebraic equation:
Now we need to solve for [tex]\( x \)[/tex]. Set up the equation:
[tex]\[ 175x + 75 = e^2 (x + 3) \][/tex]
Expand and rearrange to get all terms involving [tex]\( x \)[/tex] on one side:
[tex]\[ 175x + 75 = e^2 x + 3e^2 \][/tex]
[tex]\[ 175x - e^2 x = 3e^2 - 75 \][/tex]
[tex]\[ x (175 - e^2) = 3e^2 - 75 \][/tex]
Finally, solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{3e^2 - 75}{175 - e^2} \][/tex]
Thus, the solution for [tex]\( x \)[/tex] in the given equation is:
[tex]\[ x = \frac{3(e^2 - 25)}{175 - e^2} \][/tex]
This result can also be simplified further but relies on the values calculated within the problem setting.
Therefore,
[tex]\[ x = \frac{3 \left(e^2 - 25 \right)}{175 - e^2} \][/tex]
is the final solution for [tex]\( x \)[/tex].
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.